2022
DOI: 10.3390/rs14040879
|View full text |Cite
|
Sign up to set email alerts
|

ClassHyPer: ClassMix-Based Hybrid Perturbations for Deep Semi-Supervised Semantic Segmentation of Remote Sensing Imagery

Abstract: Inspired by the tremendous success of deep learning (DL) and the increased availability of remote sensing data, DL-based image semantic segmentation has attracted growing interest in the remote sensing community. The ideal scenario of DL application requires a vast number of annotation data with the same feature distribution as the area of interest. However, obtaining such enormous training sets that suit the data distribution of the target area is highly time-consuming and costly. Consistency-regularization-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It is noted that the parameters of VGG-16 and ResNet-50 were obtained from the official pretrained model on the ImageNet dataset [45]. While for the SSL pipeline, two prominent SSL frameworks, including CPS [53], and ClassHyPer [33] were adopted for comparison. Of which, CPS performs slight parameter perturbations between two identical base models and imposes pseudosupervision on each other for unsupervised learning; on the strength of CPS, ClassHyPer integrates ClassMix to improve the model capability.…”
Section: Results Considering Shadowsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the parameters of VGG-16 and ResNet-50 were obtained from the official pretrained model on the ImageNet dataset [45]. While for the SSL pipeline, two prominent SSL frameworks, including CPS [53], and ClassHyPer [33] were adopted for comparison. Of which, CPS performs slight parameter perturbations between two identical base models and imposes pseudosupervision on each other for unsupervised learning; on the strength of CPS, ClassHyPer integrates ClassMix to improve the model capability.…”
Section: Results Considering Shadowsmentioning
confidence: 99%
“…In particular, a few studies [31], [32] demonstrated the superiority of DL algorithms for shadow detection from RGB aerial imagery, making us confident that DL can cope with shadow problems in urban floodwater mapping. However, a huge demand for labeled training data still poses challenges in the DL domain [33]. Moreover, most relevant studies aimed to train a DL model with large quantities of labeled samples in a single location, but they may fail to generalize the same model across unseen locations due to the varying illumination and atmospheric conditions [15], [34].…”
mentioning
confidence: 99%
“…This approach not only improved the classification accuracy of semantic segmentation networks but also mitigated the negative impact of limited labeled data on network performance. In another study [ 148 ], which focused on consistency regularization in semi-supervised learning, perturbation schemes were reviewed, and prominent data-level perturbation schemes, CutMix and ClassMix (a development from CutMix), as well as model-level perturbation representatives, mean teacher (MT) and cross pseudo-supervision (CPS), were identified. Inspired by these four perturbation methods, an end-to-end semi-supervised semantic segmentation framework named “ClassHyPer” was proposed.…”
Section: Road Feature Extraction Based On Semi-supervised (Weak) Deep...mentioning
confidence: 99%
“…With perturbation-based methods, the learning process assumes that model predictions should be robust to noise. The objective function ensures that encoded feature spaces are minimally affected by a small amount of noise, as seen in studies such as [131], [132]. Manifold methods, on the other hand, operate under the assumption that some small variations in the input can yield different results.…”
Section: Intrinsically Semi-supervisedmentioning
confidence: 99%